Integrated non-invasive analysis of ceramic test sherds from the Iznik tile kilns excavation - Arli, Vesile Belgin Demirsar; Simsek-Franci, Gulsu (ELSEVIER, 2026)
Since 2010, almost every excavation season at the Iznik Tile Kilns has yielded ceramic-and tile-type samples interpreted as experimental trials carried out by ceramicists prior to the main production of the splendid Iznik masterpieces. These samples show that primary decorative colors and their tonal variations were applied using brushes of varying thicknesses, different transparent glaze compositions were tested, and holes were intentionally made, likely to evaluate glaze viscosity during firing. In this study, the analytical results obtained from 20 ceramic-type test sherds with minimal surface deterioration are presented using non-invasive analytical techniques, including digital microscopy, portable XRF, and confocal Raman spectroscopy. Both sides of the samples are decorated and glazed. Microscopic examination revealed that the glaze thickness varies between approximately 100 and 420 mu m, while the slip thickness ranges between 150 and 850 mu m. The body colors vary from white to dark beige, whereas the slips appear either quartz-rich white or clay-rich beige in tone. Except for one sample, all specimens contain a lead-alkali transparent glaze (22-40 wt% PbO). The amount of tin oxide in the glazes was found to be below 1%. Body composition analyses indicate that all samples, except one, were produced according to a stonepaste recipe, while one sample appears relatively richer in clay compared to the stonepaste group. Overall, these results suggest that the analyzed sherds represent experimental productions from Iznik workshops, likely dating to the 17th century, aimed at exploring variations in color hues and glaze compositions prior to standardized manufacture.
Keywords: pXRF; Raman; Experimental; Glaze; Iznik; Stonepaste; Paint; EUROPEAN COBALT SOURCES; SITE PXRF ANALYSIS; CHINESE PORCELAINS; COLORING AGENTS; X-RAY; TECHNOLOGY; PIGMENTS; ORIGINS; POTTERY; Chemistry